Pengembangan Media Kartu Kuartet untuk Keterampilan Menulis Kalimat Sederhana - Arfiana, Rizma; Nanang; Iqnatia; Afakh (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2024)
This study aims to describe the quality of learning media produced in terms of validity and effectiveness as well as describe students' responses to quartet card learning media for simple sentence writing skills.  The development of quartet card media uses the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This research was conducted at UPT SD Negeri 23 Gresik. The subjects of this research were fourth grade students of UPT SD Negeri 23 Gresik. The techniques used for data collection are media validation and questionnaires. The data analysis techniques used were media and material expert validation analysis, student response questionnaire analysis, and media effectiveness analysis. As a result of the research, two media experts who are lecturers in the Elementary School Teacher Education study program and two material experts from classroom teachers IV UPT SD Negeri 23 Gresik declared the quartet card learning media for simple sentence writing skills to be "very valid" in terms of both validity and effectiveness. 85.71% and 82.85%, respectively, were the scores of the first and second media expert validators. In the meantime, 95% was the score obtained by the first material expert validator and 92.25% by the second. The medium was deemed effective when 90.7% of the students' completed assignments met the required standards. The quartet card learning media received an overall response rate of 87.79% from 43 students, indicating that the media was deemed "very positive".